HISTOMORPHOLOGICAL FEATURES OF VARICOSE VEINS IN YOUNG MALE POPULATION: A PROSPECTIVE CASE CONTROL STUDY IN SOUTH INDIA - REMYA K; SUNIL KUMAR Y; RAJESH BALLAL (International Journal of Pharma and Bio Sciences, 2014)
Varicose veins are tortuous, widened veins in the subcutaneous tissues of lower limbs and are often easily visible. The primary cause of varicose vein formation is not clear. Previous histological studies of varicose veins demonstrate the disorganization of the venous wall. This is because of varying degrees of intimal thickening, infiltration of fibrous tissue in the muscular layers, accumulation of collagen and fragmentation of elastic fibres.The aim of the study was to compare the histological changes in varicose veins with normal veins.Materials and methods: Patients of 18-35 years undergoing stripping surgery for varicose veins were selected for the study and compared with normal veins extracted from similar group undergoing herniorrhaphy for groin hernia. Biopsies received were subjected for histological examination using haematoxylin & eosin, van- giesen and verhoff stains.Histological examination showed changes in intima, media, adventitia and smooth muscle. Intima & adventitia showed accumulation of collagen fibers. There was disturbed architecture of smooth muscle fibres arranged in media.Changes were present in all the layers including the adjacent areas of the affected varicose veins.This suggests primary weakness in vein wall as cause of varicosity. However more studies have to be carried out to obtain results than can lead to generalizations.